(untitled) (Research, Society and Development, 2020)
The filter cake is a residue from the sugarcane processing industry and has shown excellent results for its use in fertilizing agricultural crops. The objective of this work was to evaluate the growth and development of okra seedlings produced with different proportions of filter cake as a substrate. The experiment was carried out under greenhouse conditions in a completely randomized design (CRD) with five treatments and five replicates (5x5). The treatments consisted of five proportions for filling the tubes with 0, 25, 50, 75 and 100% filter cake. The filter cake was obtained in a sugar and alcohol industry near the municipality of Santa Helena de Goiás. Were evaluated plant height (PH), stem diameter (SD), number of leaves (NL), root length (RL), aerial fresh mass (AFM), fresh root mass (FRM), aerial dry mass (ADM) and the dry root mass (DRM). The data were submitted to analysis of variance by the F test (p <0.05) and in cases of significance, regression analysis was performed for the filter cake proportions, using the SISVAR statistical software. The fertilization with filter cake on okra seedlings was significant at the level of 5% probability for the RL and 1% probability for PH, SD, NL, AFM, FRM, ADM, DRM. The maximum PH, SC, NL, RL, AFM, ADM, DRM was obtained with the filter cake proportions of 55.83; 49.58; 35.55; 47.25; 50.17; 48.5; 58.5 and 45.00%. The use of residues from the sugar and alcohol industry can be used for fertilizing okra seedlings. It is recommended to use the ratio of 55% filter cake and 45% soil, in that dose the okra seedlings show the best growth and development.